(untitled) (Fiep Bulletin - online, 2011)
The objective of this study was the evaluation of the psychomotor development of 30 children aged from 3 to 4 years old in a private school in Lages / SC, 15 girls and 15 boys. For the evaluation of the psychomotor development the Motor Development Scale was used - EDM (Rosa Neto, 2002), which assesses the following areas: fine motricity, global motricity, body scheme, spatial organization, temporal organization and symmetry. Through this scale, it is possible to obtain the General Motor Quotient (QMG) of each child, which is rated at 7 levels: "very superior", "superior", "high normal", "normal average", "low normal", " low "and" very low ". The results show that most children (n=21) reached normality in relation to psychomotor development, with levels in "normal average" (n=15) and "low normal" (n = 6), corroborating with other studies. It should be noted, however, that some children have reached levels below normal, with levels "low" (n=6) and "very low" (n=3), which may represent a warning sign for the above and the probable need for specific activities targeted under motor and neuropsychological. It was evident in this study the importance of psychomotor evaluation in students in the kindergarten, as a preventive method to detect changes and suggest early interventions